INTEGRASI LAGU DAERAH PAPUA SEBAGAI PELESTARIAN BUDAYA DALAM PEMBELAJARAN IPS UNTUK MENGUATKAN IDENTITAS BUDAYA PESERTA DIDIK DI SD - Selvia Yusuf (FKIP Universitas Cenderawasih, 2025)
Abstract: This article examines the urgency of preserving local culture through education, Papuan cultural identity, cultural identity in elementary school students, the educational function of Papuan folk songs, and strategies for integrating folk songs in IPS learning. The discussion shows that Papuan folk songs can be an effective medium for strengthening cultural awareness, fostering pride, enhancing understanding of local history, and instilling positive character traits in students. Various strategies such as contextual learning, integrative thematic learning, project-based learning, and collaborative learning can enhance the effectiveness of this integration. Furthermore, the integration of folk songs has cognitive, affective, social, psychomotor, and long-term impacts on preserving Papuan cultural identity. Therefore, the use of Papuan folk songs in social studies learning is an important approach to developing a young generation of Papuans with character, culture, and a strong sense of identity. Keywords: Papuan Regional Songs; Elementary School Social Studies; Cultural Identity; Cultural Preservation; and Local Culture-based Learning. Abstrak: Artikel ini mengkaji urgensi pelestarian budaya lokal melalui pendidikan, identitas budaya Papua, identitas budaya pada peserta didik SD, fungsi edukatif lagu daerah Papua, serta strategi integrasi lagu daerah dalam pembelajaran IPS. Pembahasan menunjukkan bahwa lagu daerah Papua dapat menjadi media efektif dalam memperkuat kesadaran budaya, menumbuhkan rasa bangga, meningkatkan pemahaman sejarah lokal, serta menanamkan karakter positif pada peserta didik. Berbagai strategi seperti pembelajaran kontekstual, tematik integratif, project-based learning, dan pembelajaran kolaboratif dapat meningkatkan efektivitas integrasi tersebut. Selain itu, integrasi lagu daerah memberikan dampak kognitif, afektif, sosial, psikomotorik, dan jangka panjang terhadap pelestarian identitas budaya Papua. Dengan demikian, penggunaan lagu daerah Papua dalam pembelajaran IPS menjadi salah satu pendekatan penting untuk membangun generasi muda Papua yang berkarakter, berbudaya, dan memiliki identitas diri yang kuat. Kata Kunci: Lagu Daerah Papua; IPS SD; Identitas Budaya; Pelestarian Budaya dan Pembelajaran Berbasis Budaya Lokal.